The problem of hypersensitivity to vitamin preparations - S.V. Zaikov; G.L. Gumeniuk; L.V. Veselovsky (Civic Union "Communicable Diseases Intensive Care Association", 2021)
ABSTRACT. The problem of the development of adverse reactions as a result of the use of diagnostic and medicinal products (drugs) is becoming increasingly important. Patients more often report reactions to local anesthetics (43.2 % of cases), antibiotics (18.8 %), nonsteroidal anti-inflammatory drugs (9.7 %), other drugs (28.4 %), B vitamins (4-5 %). It is important to understand that hypersensitivity (HS) to vitamin preparations (VP) is very common, according to patients, but not so often confirmed by their in-depth allergy examination. Basic data on HS before the VP were obtained in the 80-90s of the 20th century, but since then the situation has changed radically. The frequency of HS on these drugs is based on medical history when patients use multicomponent VP for oral administration, allergens in which may be other components (shell tablets and capsules, metal salts, flavors, sweeteners, dyes, preservatives). The causative allergens in the injectable forms of VP can also be auxiliary ingredients of the drug, in particular lidocaine and benzyl alcohol. There are only a few scientific publications with the appropriate evidence base for HS to individual VP, more often B vitamins. The clinical picture of HS reactions to VP is diverse (systemic, cutaneous, respiratory, rarely other visceral manifestations). They can develop both immediately and in a delayed type. Part of the VP (B vitamins, vitamin K) can cause the development of anaphylaxis with fatal consequences. VP, as a rule, do not belong to vital drugs therefore it is possible for this reason till now in real clinical practice insufficiently developed methods of allergodiagnostics both in vivo (skin, provocative tests), and in vitro (laboratory tests) among patients with suspicion for the development of HS to VP. It is not possible to perform allergy diagnostics in persons who have taken complex VP, so there is a problem of hyperdiagnosis of drug allergy to them. Therefore, the problem of determining the true allergic reaction in patients who report the development of a history of HS to VP remains relevant. As a rule, after the development of any adverse reaction during the reception of VP on the patient hangs the label "allergy to vitamins" for life without further allergy examination. That is why the problem of HS to VP needs further study.